2018
DOI: 10.2135/cropsci2017.05.0324
|View full text |Cite
|
Sign up to set email alerts
|

Can Cover or Forage Crops Replace Fallow in the Semiarid Central Great Plains?

Abstract: Growing a crop in place of fallow may improve soil properties but result in reduced soil water and crop yields in semiarid regions. This study assessed the effect of replacing fallow in no‐till winter wheat (Triticum aestivum L.)–fallow with cover, forage, or grain crops on plant available water (PAW), wheat yield, grain quality, and profitability over 5 yr, from 2007 to 2012. Plant available water at wheat planting was reduced the most when the fallow period was the shortest (i.e., following grain crops) or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
219
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(233 citation statements)
references
References 48 publications
10
219
2
2
Order By: Relevance
“…Whereas biomass production for pea and vetch were comparable to cover crop production in the Central Great Plains (Holman et al., 2018; Nielsen et al., 2015a), seeding rates used in this study were at least 65% lower for pea and 20% lower for vetch. Mirsky et al.…”
Section: Resultsmentioning
confidence: 45%
See 2 more Smart Citations
“…Whereas biomass production for pea and vetch were comparable to cover crop production in the Central Great Plains (Holman et al., 2018; Nielsen et al., 2015a), seeding rates used in this study were at least 65% lower for pea and 20% lower for vetch. Mirsky et al.…”
Section: Resultsmentioning
confidence: 45%
“…They also found crimson clover to generally produce less biomass than peas and vetch. Biomass production in the Central Great Plains of Kansas was 0–1052 kg ha −1 for vetch and 0–982 kg ha −1 for pea (Holman et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the differences in CC functional groups within a mixture, the enhanced resource efficiency could lead to greater CC biomass production, which may then differently impact soil ecosystem services (Smith et al., 2014; Wortman, Francis, & Lindquist, 2012). Published studies comparing CC biomass production between single species and mixes found no differences in biomass production (Holman et al., 2018; Hunter et al., 2019; Murrell et al., 2017; Wortman et al., 2012), increased biomass production with mixes compared to some single species (Murrell et al., 2017; Smith et al., 2014), or decreased biomass production (Appelgate, Lenssen, Wiedenhoeft, & Kaspar, 2017; Finney, White, & Kaye, 2016; Hunter et al., 2019). Several studies evaluated CC mix biomass production and its effects on weed suppression and effects on main crop yields (Finney et al., 2016; Noland et al., 2018; Smith et al., 2014; Wortman et al., 2012), but those investigating the effects of CC mixes on soil properties are fewer.…”
Section: Introductionmentioning
confidence: 95%
“…Preliminary results indicated that yield reductions as high as 50% can occur when summer fallow was replaced by a CGM in Utah (unpublished data). Recent work showed that CGMs in Kansas could replace summer fallow successfully where grain yield potential exceeded 3.5 Mg ha −1 (Holman et al., 2018). This is considerably higher than yields typically achieved by farmers in semi‐arid and arid regions (Reeve et al., 2012).…”
Section: Dual‐use Cover/green Manure Cropsmentioning
confidence: 99%